Satisfaction with obstetric care. Patient survey in a family practice shared-call group. - Shapiro, J. L. (College of Family Physicians of Canada, 1999)
OBJECTIVE: To examine patients' satisfaction with their obstetric care in a family medicine shared-call group. DESIGN: A survey was given to a convenience sample of patients who came to see their doctors over a 6-week period. SETTING: Brameast Family Practice in Brampton, Ont, where eight doctors participate in a shared obstetrics call group with 16 other physicians, each taking call 1 day in 23 days. PARTICIPANTS: Mothers in the practice who had delivered in the previous 8 months. MAIN OUTCOME MEASURES: Demographic data, interventions during delivery, and satisfaction ratings. RESULTS: Of the 70% of women who responded, 96% were delivered by a doctor other than their own. Eighty-eight percent of these women were satisfied with their medical care at delivery and 96% were satisfied with their prenatal care. Nearly 79% said they would choose this shared-call group again. CONCLUSIONS: This pilot study demonstrated a high level of patient satisfaction with obstetric care, despite the fact that most patients were delivered by a doctor other than their own. Family practice groups sharing obstetric call offer a feasible alternative for physicians who wish to avoid the interference with lifestyle and office appointments that practising obstetrics usually entails.